Investigation of the Relationship between Inflammatory Factors CRP, IL-6 and IL-1â and Major Depressive Disorder: A Hospital Based, Case-Control Study - Ather Muneer; Furqan Ahmad; Mariam Tariq; Kazim Abbas; Asad Ali; Ambreen Zahoor (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: The present study aims to investigate the relationship of these factors and major depres- sive disorder in a sample of patients presenting to the psychiatry department of the teaching hospital of a private medical college in Islamabad, Pakistan. Methods: Using convenience sampling a total of 50 participants were included in the study which comprised of 25 patients with major depressive disorder (MDD) and 25 matched healthy controls (HC). The severity of depression was determined with the help of Hamilton Rating Scale for Depres- sion (HRSD) while the demographic details of the participants were collected with the help of a pro- forma. The pro-inflammatory markers (CRP, IL-6 and IL-1â) were measured in the serum by taking peripheral venous samples from both cases and controls. Statistical analysis was performed by using SPSS, version 22. Results: Patients with MDD had significantly higher levels of the pro-inflammatory factors as com- pared to healthy controls. In HC the levels of pro-inflammatory cytokines were not raised to any significant degree, while these were consistently higher in MDD patients with acute depressive episodes (two sample t test 2-tailed significance d" 0.01). Conclusion: This study showed that sensitive indicators of inflammation were higher in the local pa- tients with MDD. Our study lends support to the inflammatory hypothesis of major depression, so that there is a further need to investigate this avenue. In this manner it would be possible to discover much needed biomarkers, while opening new paths to more effective therapeutics of this recalcitrant disorder.